2016
DOI: 10.4149/212_140820n391
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors of cisplatin induced ototoxicity in adult patients

Abstract: Ototoxicity is an important adverse effect of using Cisplatin (cis-diamminedichloroplatinum) (CDDP) as a form of chemotherapy. The clinical picture of CDDP induced ototoxicity includes perceptive hearing impairment (reversible or permanent) and tinnitus. Ototoxicity manifests with considerable variability between patients. The objective of this prospective study was to investigate a possible genetic background to this variability. We assessed ototoxicity induced by therapeutic doses of CDDP in adult patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, others were unable to confirm these findings ( Table and Table ). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section “Confounding Factors.” Of note, when excluding cohorts of patients who all received cranial irradiation or that included adult patients, the findings from all but one study showed that TPMT rs12201199 was either significantly more frequent in cases when compared with controls, or trended toward significance ( P = 0.07) . On closer examination of the small cohort of patients ( n = 41) that deviated from the pattern of increased risk, it was observed that only CIO cases carried nonfunctional TPMT*3 alleles.…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, others were unable to confirm these findings ( Table and Table ). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section “Confounding Factors.” Of note, when excluding cohorts of patients who all received cranial irradiation or that included adult patients, the findings from all but one study showed that TPMT rs12201199 was either significantly more frequent in cases when compared with controls, or trended toward significance ( P = 0.07) . On closer examination of the small cohort of patients ( n = 41) that deviated from the pattern of increased risk, it was observed that only CIO cases carried nonfunctional TPMT*3 alleles.…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
“…In addition, von Stechow et al 29 demonstrated that TPMT expression is induced by cisplatin in embryonic stem cells, providing further evidence for this drug-gene relationship. The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, 23,[30][31][32][33] others were unable to confirm these findings 9,13,16,30,[32][33][34][35][36] (Table 1 and Table S1). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section "Confounding Factors."…”
Section: Supporting Evidence For the Roles Of Comt And Tpmt In Ciomentioning
confidence: 99%
“…36 However, this report contradicts a previous study demonstrating that the null phenotype for GSTT1 was protective against cisplatin ototoxicity. 37 MSH3 GG or GA and GT haplotype of EXO1 rs1047840 and rs9350 SNPs predisposed patients to significantly greater probability of pronounced ototoxicity from cisplatin than MSH3 AA genotype and other EXO1 haplotypes, respectively. 32 Genetic changes associated with better hearing outcomes have also been reported.…”
Section: Pharmacogenomicsmentioning
confidence: 94%
“…8 Genetic factors also may contribute to individual vulnerability to ototoxicity. 9,10 The potential for increased ototoxicity occurs if drugs and/or treatment methods are used in combination. Cranial radiation combined with cisplatin exacerbates the progression of cochlear damage and associated hearing loss.…”
mentioning
confidence: 99%